Temporal variation of peanut worm (Siphonosoma australe-australe) reproduction in Toronipa Beach of Southeast Sulawesi, Indonesia - BAHTIAR BAHTIAR; YNGWY EZRA JIWANI; MUHAMMAD NUR FINDRA; ERMAYANTI ISHAK (Society for Indonesian Biodiversity, 2024)
Abstract. Bahtiar, Jiwani YE, Findra MN, Ishak E. 2024. Temporal variation of peanut worm (Siphonosoma australe-australe) reproduction in Toronipa Beach of Southeast Sulawesi, Indonesia. Biodiversitas 25: 2533-2540. The peanut worm Siphonosoma australe-australe in Toronipa Beach, Konawe District, Southeast Sulawesi, Indonesia is constantly facing ecological pressure. However, a limited understanding of its reproductive pattern hinders the development of a management plan. This study aimed to determine the sex ratio, GML (Gonad Maturity Level), GSI (Gonad Somatic Index), and the size of the peanut worm at early gonad maturity in Toronipa Beach, Southeast Sulawesi, Indonesia. Worms were collected using a hand spade, and the length and weight were measured using a ruler (accuracy of 0.5 cm) and an analytical balance (accuracy of 0.0001 g), respectively. Dissection was then conducted to observe eggs and sperm in the coelom. Additionally, water quality measurements were taken simultaneously with worm sampling. A total of 467 peanut worms were collected, and data were analyzed using standard formulas. The results showed that during the 11-month duration of this study, the sex ratio of peanut worms was imbalanced, as females were more than males. Aside from being dioecious, these worms were hermaphroditic and parthenogenous; the gonad maturity analysis showed various stages (I-IV) in peanut worms throughout the study. The highest level of gonadal maturity for male and female peanut worms was observed in August and September at Toronipa Beach. The first gonad maturity for male peanut worms occurred at 12.4-13.4 cm, while females matured at 13-13.5 cm. Throughout the year, gonad maturity and spawning were supported by environmental factors, such as temperature and organic matter that ranged from 30-32°C and 2.06-4.31 mg/L, respectively. Reducing harvesting activities during the peak spawning months is recommended to maintain the peanut worm population.